AB1060 Whipple disease with initial presentation as non-erosive seronegative polyarthritis: a case report from a single centre. (12th June 2018) - Korendovych, V.; Schoenherr, J.; Duerdoth, T.; Schumann, F.; Blendea, D.; Spiridon, D.; Abdellatif, H.; Sarholz, M.
Abstract : Background: Whipple disease (WD) is a rare disease caused by the bacterium Tropheryma whipplei (TW), which manifestations may range from joint and GI-tract involvement to severe neurological complications. Objectives: To present a clinical case of WD with non-erosive seronegative polyarthritis, sacroiliitis, abdominal and CNS involvement, and immune reconstitution inflammatory syndrome after antibiotic therapy. Methods: Case report. Prospective follow-up of the patient E. with WD, who was diagnosed HLA-B27-negative nonerosive seronegative rheumatoid arthritis in 2013. The disease was partially responsive to glucocorticoids with temporary effect to different DMARDs (MTX, leflunomid, etanercept, abatacept, tocilizumab either as monotherapy or in combination). Results: A 54 y.o. male patient E. was admitted to the Rheumatological department with complaints of joint swelling, low back pain, weight loss, diarrhoea, headache and low grade fever. Peripheral joint arthritis appeared about 4 years ago with progressive worsening of general condition and development of additional complaints during the past year. From 2013 to 2017 the patient received in-hospital and outpatient treatment because of active seronegative polyarthritis without sufficient effect. On admission: clinical examination and joint ultrasound (US) investigation revealed the signs of polyarthritis. Neurological evaluation showed organic psychiatric disorder with signs of pseudodementia, bradykinesia without focal neurological deficits. Because of both incomplete responsiveness to DMARD-therapy and suspicion of chronic infection or malignant neoplasm, abdominal US and transthoracic echocardiography, gastroscopy, colonoscopy, immunofixation, bone marrow biopsy, chest X-ray and bone scintigraphy, tests for viral hepatitis (B, C), HIV, Lues and QFT-Tb were performed, however without objective evidence of the cause. PET-CT was performed as well, but showed no signs of malignancy or infection. MRI revealed bifrontal brain atrophy, low-grade bilateral sacroiliitis and degenerative changes of the cervical spine. For differential diagnosis PCR stool investigation for TW was performed and was positive. Upon the suspicion of WD duodenoscopy with duodenal biopsy were done. Histological examination showed PAS-positive macrophages, typical for WD. Immunohistochemical analysis also supported the diagnosis. PCR investigation of liquor and synovial fluid from ankle joint for TWi were also positive. Antibiotic treatment using a 2 week course of parenteral Ceftriaxon 2 g/day was initiated. On the third day of the treatment the patient developed immune reconstitution inflammatory syndrome with febrile temperature and increased inflammatory markers. The symptoms regressed after additional prednisolon 20 mg/day prescription. Because of organic brain syndrome, administration of Co-trimoxazole was recommended. Under the antibacterial therapy the patient had rapid positive response. PCR stool test in October 2017 didn't detect TW. Conclusions: This presentation emphasises the importance of excluding a rare infection as a cause of atypical inflammatory arthropathy. In patients with seronegative rheumatoid arthritis or axial and peripheral spondyloarthritis, who don't adequately response to immunosuppression, Whipple disease should be taken into account. Disclosure of Interest: None declared